“Thinking Pure Life”: Dialectics as Grammatical Critique - Pennycook, Pedro (Revista Eletrônica Estudos Hegelianos, 2024)
I argue that Hegel’s concept of freedom requires the dissolution of dichotomies between history and nature. Ultimately, dissolving them would lead to an embodied concept of agency, whereby the singularity of each concrete organism finds normative expression within a free form of life. For that, I suggest that the dialectical thesis of speculative identity intertwines social critique with the critique of philosophical language. I shall call this procedure a “grammatical critique”, revealing Hegel’s shift to a vital normativity as its therapeutic moment. That will allow me to present the social pathologies of dualistic forms of life as a withholding of the fluidity of organic nature, instantiated in the body-mind split. I then turn to Adorno’s notion of “recording nature”, arguing that it fulfills the dialectical criteria for free a form of life, that is: where its agents are able to reflexively enact their vital normativity
Keywords: grammatical investigation; natural history; embodied agency; forms of life; nature in Hegel